The critical points in induction of experimental autoimmune uveitis - Klimova, Aneta; Seidler Stangova, Petra; Svozilkova, Petra; Forrester, John V; Klaska, Izabela; Heissigerova, Jarmila (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2016)
BACKGROUND: Autoimmune uveitis is a leading cause of visual impairment in developed countries in patients of working age. Animal models of experimental autoimmune uveitis (EAU) have been established to serve as a useful template for novel therapeutic approaches. METHODS: Experimental autoimmune uveitis is induced in C57BL/6 mice by subcutaneous application of interphotoreceptor retinoid binding protein in complete Freund's adjuvant and pertussis toxin. Clinical and histological grading is used to assess the inflammation intensity of EAU. RESULTS: The protocol of induction of EAU in mice hides several important aspects, which are crucial for developing the disease. These details have to be addressed to ensure reproducible disease induction. We describe our experience in establishing the model by pointing out the critical steps in EAU protocol which we found important. CONCLUSION: The mouse model of EAU has practical value for preclinical studies, is robust and well established. However, the induction of inflammation of the eye can be quite challenging when important details of the protocol are not recognized and adhered to.
Keywords: Animals; Female; Autoimmune Diseases; ženské pohlaví; proteiny vázající retinol; Adjuvants, Immunologic; Freund's Adjuvant; Eye Proteins; autoimunitní nemoci; Irritants; oční proteiny; uveitida; induction protocol; modely nemocí na zvířatech; dráždivé látky; chronic posterior autoimmune uveitis; Uveitis; C57BL/6 mouse strain; Disease Models, Animal; Pertussis Toxin; Freundovo adjuvans; chronická nemoc; pertusový toxin; zvířata; Mice, Inbred C57BL; Retinol-Binding Proteins; Chronic Disease; adjuvancia imunologická; experimental autoimmune uveitis; myši inbrední C57BL; mouse model